Using Matching Grants to Facilitate Corporate-University Research Linkages: A Preliminary Examination of Outcomes from One Initiative - Bell, Stephen (Canadian Journal of Higher Education, 1990)
In the 1980’s the issue of corporate-university linkages has received markedly increased attention from governments, corporations, and universities. From government’s perspective, the drive to enhance corporate-university linkages is derived from the belief that these linkages will contribute to economic competitiveness. One method that has been used by government to encourage this interaction is through the provision of matching grants. Using public finance theory as the conceptual basis, the paper examines the preliminary outcomes of one government’s matching grant initiative. Through a compilation of data on university research revenues on corporate contract research and a questionnaire to companies that placed the research contracts in universities, the paper shows that matching grants, in the manner provided by the BILD program, may not be an effective mechanism to promote corporate-university research linkages. The paper concludes with some suggestions for further research and discusses the conceptual and methodological hurdles that can be encountered when attempting to asses the outcomes of a matching grant program, particularly as applied to corporate-university linkages.